Design, synthesis and biological evaluation of small molecule-based PET radioligands for the 5-hydroxytryptamine 7 receptor1. Issue 25 (21st March 2015) - Tiwari, A. K.; Yui, J.; Pooja; Aggarwal, S.; Yamasaki, T.; Xie, L.; Chadha, N.; Zhang, Y.; Fujinaga, M.; Shimoda, Y.; Kumata, K.; Mishra, A. K.; et al.
<x xml:space="preserve">Abstract</x> A new prospective approach for PET imaging of 5-HT7 by a small molecule ligand.